Antimicrobial Stewardship Programs in Pediatric Intensive Care Units: A Systematic Scoping Review - Cecilia Liberati; Giulia Brigadoi; Elisa Barbieri; Carlo Giaquinto; Daniele Donà (Antibiotics, 2025)
Objectives: We aimed to summarize the current state of antimicrobial stewardship (ASP) and diagnostic stewardship programs (DSPs) implemented in pediatric intensive care units (PICUs). Methods: Embase, MEDLINE, Scopus and the Cochrane Library were searched, including studies from 1 January 2007 to 20 February 2024. Studies were included in the review if they assessed the implementation of an ASP or a DSP in a PICU. Identified references were downloaded into Rayyan software, and data were extracted using a standardized data collection form. Results: 18 studies were included; 13 described an ASP intervention, and 5 described a diagnostic stewardship intervention. Most studies were retrospective and adopted a persuasive strategy for ASP, reporting positive effects on antimicrobial consumption. However, studies were dramatically heterogeneous in terms of intervention type, outcomes and metrics used, limiting the possibility of a broader comparison. Diagnostic stewardship studies included mainly the impact of biomarkers and pathogen testing panels without significant impact on antibiotic prescription patterns. Antimicrobial resistance changes were not described by the majority of studies. Conclusions: the implementation of ASP in PICUs is still limited, with significant variability in the metrics used to evaluate outcomes. To enhance the effectiveness of these programs, it is crucial to harmonize reporting metrics to allow an adequate comparison of results and to find the best strategies to inform ASP in PICUs.